Child Odors and Parenting: A Survey Examination of the Role of Odor in Child-Rearing - Okamoto, Masako; Shirasu, Mika; Fujita, Rei; Hirasawa, Yukei; Touhara, Kazushige (PLOS ONE, 2016)
Parental caregiving is critical for the survival of our young and continuation of our species. In humans, visual and auditory signals from offspring have been shown to be potent facilitators of parenting. However, whether odors emitted by our young also influence human parenting remains unclear. To explore this, we conducted a series of questionnaire surveys targeting parents with children under 6 years old. First, we collected episodes on experiencing odors/sniffing various parts of a child’s body (n = 507). The prevalence of experiencing events described in those episodes was examined in a separate survey (n = 384). Based on those results, the Child Odor in Parenting scale (COPs) was developed, and subsequently used in the main survey (n = 888). We found COPs to have adequate content validity, concurrent validity, and reliability. Responses to the COPs demonstrated that parents, especially mothers with infants, are aware of odors from their offspring, and actively seek them in daily child-rearing. The factor structure and content of the COPs items indicated that child odors have both affective and instrumental roles. Affective experiences induce loving feeling and affectionate sniffing, while instrumental experiences pertain to specific hygienic needs. The head was the most frequent source of affective experiences, and the child’s bottom of instrumental. Each was experienced by more than 90% of the mothers with a child below 1 year of age. Affective experiences significantly declined as the child grew older, possibly associated with the decline of physical proximity between parents and child. This age-related decline was not prominent for instrumental experiences, except for the bottom, which significantly declined after 3 years of age. The present findings suggest that child odors play roles in human parenting, and that their nature and significance change during the course of a child’s development.